Adsorption of Reactive Brilliant Blue XBR onto Polymeric Adsorbents from Single- and Binary-Solute Solutions - Lu Zhaoyang; Long Chao; Li Aimin; Jiang Zhenmao; Liu Wei; Chen Jinlong; Zhang Quanxing (Adsorption Science & Technology)
A non-ionic polymer adsorbent (NPA) and its aminated polymeric adsorbent (APA) were prepared and characterized towards adsorption from aqueous solution. Two adsorbates, Reactive Brilliant Blue XBR and 2,4-diaminobenzene sulphonic acid (ABSA), were chosen as adsorbates for competitive adsorption from single-solute solution and binary-solute systems onto the two adsorbents prepared. The results showed that APA, the polymer obtained after amination, exhibited a higher adsorption capacity than NPA towards XBR from the single-solute solution. However, in binary-solute solution adsorption, the presence of ABSA reduced the adsorption capacity towards XBR due to direct competition between XBR and ABSA for the same adsorption sites. This resulted in similar adsorption capacities towards XBR for NPA and APA. Moreover, the adsorption selectivity coefficients obtained for XBR onto ABSA in simultaneous adsorption tests suggested that NPA exhibited more favourable adsorption properties towards the adsorption of XBR from binary-solute systems than APA.